EVALUATION OF THE LEVEL OF JOB SATISFACTION AMONGST TEACHING FACULTY IN A MEDICAL COLLEGE SETTING IN INDIA (Journal of Forensic Medicine & Toxicology, 2021)
Background: The level of job satisfaction of professionals determines their productivity in an organization. This serves as an important step to improve the health, progress, performance and development of the citizens, and henceforth of a nation. The understanding of the factors important in labor intensive organizations, such as health care establishments, and further in more demanding specialties. Aims & Objectives: 1) To evaluate the level of job satisfaction amongst the orthopedic residents and faculty, and determine the factors associated with it in a teachinghealth care setting. 2) To determine the relationshipbetween the level of job satisfaction and socio- demographic characteristics of the surgeons. 3) To suggestaction/s (if any) for the improvement of the level of the jobsatisfaction.Materials & Methods : Data was collected using a pretested structured questionnaire from 50 orthopedic surgeons employed in tertiary care health setting, associated with medical college. The response to eachquestion was devised to be answered via Likert scale.The
Keywords: Doctors; Job satisfaction; Teaching hospital; Ergonomics; Mental fatigue